Comparative study on pathological changes in sheep and goats experimentally infected with Haemonchus Contortus - Jirata Shiferaw Abosse; Getachew Terefe; Bethlehem Mesfin Teshale (BMC, 2022)
Abstract Background The parasites causes localized and generalized infections to the host depends on the parasite attachment organs, depth of penetration, site of location and worm burdens. Methods The experimental study was done between December, 2019 and April, 2020 in the fly-proof experimental animal facility located in the premise of the College of Veterinary Medicine and Agriculture at Bishoftu, Ethiopia. A total of 14 male goat (G1 and G2) and 14 male sheep (G3 and G4) were allotted in to four equal groups. Single dose of 10,000 of infective larvae of Haemonchus contortus (L3) was orally administered to each animal in G1 and G3. Parameters such as body weight, PCV, haemoglobin, worm count, serum total protein, serum albumin, alkaline phosphatase and aspartate aminotransferase were measured. Moreover, histopathological sections were stained and examined for general changes as well as for changes in specific cells such as tissue eosinophilia and parietal cell population. Results The findings show that 1) All infected sheep and goats developed the infection with higher mean worm burden in goats (5590) than sheep (2887) and the difference was significant (P < 0.05); 2) All infected sheep and goats exhibited a progressive anaemia; the level being more severe in goats than in sheep (P < 0.05) with mean PCVs of 13 and 18.6% respectively; 3) While body weight gain was minimal in sheep, goats have lost significant weight compared to pre-infection levels, to control animals or in relation to infected sheep (P < 0.05); 4) analysis of biochemical changes revealed marked reduction in serum total protein and albumin which was much more significant in goats than in sheep (P < 0.05); 5) the abomasum of infected sheep and goats have shown thickening, nodule development, eosinophilic infiltration and damage to parietal cells. Tissue eosinophilia was more prominent in sheep while parietal cell loss was severe in goats. Conclusion In conclusion, goats under experimental infection and similar management condition with sheep develop much more severe infection and associated pathology compared to sheep and hence deserve special attention.